Does performance on the ABLA test predict receptive name recognition in children with autism? - Roy-Wsiaki, Genevieve (2010)
Researchers have hypothesized that for people with autism, the deficits in learning certain tasks may be a function of deficits in learning the prerequisite auditory, visual and motor discriminations. The Assessment of Basic Learning Abilities (ABLA) Test is a useful tool by which these discriminations are assessed. This study investigated whether performance on ABLA Level 6, an auditory-visual discrimination, predicts performance on a receptive language task with children with autism. Participants included five children who passed ABLA Level 6, four children who passed ABLA Level 4 but failed ABLA Level 6, and one child who passed ABLA Level 3 but failed ABLA Level 4. Standardized prompting and reinforcement procedures were used to attempt to teach each participant to respond correctly on ten name-recognition tasks. During a task pictures of two objects were placed in randomly alternated left-right positions, and a child was required to point to the picture that was named. Training on a task continued until either a pass or a fail criterion was met, whichever came first. Three of the Level 4 participants passed all ten of the picture name recognition tasks, and one passed eight of the ten tasks. The Level 3 participant passed two of the ten tasks. All five of the Level 6 participants passed all picture name recognition tasks. The difference in performance between children at ABLA Level 4 and Level 6 was not significant at the .05 level. These results suggest that children with autism at ABLA Level 4 or 6 are approximately equally capable of learning receptive name recognition tasks.